Evaluation of macroparticles and nanoparticles of zinc and zinc oxide’s toxicity based on the Artemia salina model - Serikbai, A.T.; Aitkulov, А.М.; Zeynidenov, A.К.; Kystaubaeva, Z.T. (Fundamental and Experimental Biology, 2022)
This article is devoted to the study of the effect of macroparticles and nanoparticles of zinc and zinc oxide on animals. The toxicity of pollutants to the fauna of aquatic ecosystems was assessed in course of a laboratory experiment. The test objects, the larvae of crustaceans of Artemia salina, were exposed to the particles of zinc (Zn) and zinc oxide (ZnO). The particle content in the water was 5 mg, 10 mg, 20 mg per 100 ml. The obtained results of the research indicate that the zinc and zinc oxide nanoparticles in the studied concentrations show a slight degree of toxicity during the 48-hour experiment period. The macroparticles of these substances have higher toxic properties for eggs and larvae of Artemia salina.